Cowboy strong - Brown, Carolyn, 1948- (Brown, Carolyn, 1948- Longhorn Canyon novel., 2020)
"Alana Carey can out-rope, out-ride, and challenge even the best Texas cowboy. Working on her father's ranch for most of her life has made her tough as nails, but she does have one soft spot -- and his name is Paxton Callahan. And with Pax back in town, Alana's old feelings have returned with a vengeance. But she barely has time to process her attraction for the hunky cowboy before her father falls ill and presents her with an ultimatum. Alana's father wants her married and settled before he passes away, and she isn't about to break a dying man's heart. Paxton Callahan has been in love with Alana since ... forever, and he's finally ready to stop running from his feelings. It's been ten years since he's seen the sexy cowgirl, and now that he's living next door, the electricity between them is about to set the whole Texas panhandle on fire. When Alana presents him with a crazy proposal -- to pretend to be her fiance so her father can die in peace -- Paxton can't refuse. But as the faux-wedding day draws near, and her father's health improves, Alana and Paxton must decide whether to commit to the charade or finally admit their love is the real deal."--Page 4 of cover